A randomized comparison of the 3 Papanicolaou smear collection methods - (:unkn) unknown (My University, 1995)
The purpose of this study was to compare the effectiveness of 3 cervical smear sampling devices for obtaining acceptable yields of endocervical cells in Papanicolaou smears. In a randomized, controlled clinical trial, we collected 346 smears over a 6-month period, 110 with the Cervex brush, 125 with the cotton swab plus Ayre spatula and 111 with the Cytobrush plus Ayre spatula. The Cytopathology Laboratory, blinded to the Papanicolaou smear method, screened the smears using the Bethesda system guidelines. Statistical analyses were performed using the Pearson X2 and analysis of variance tests. There was an increased detection of endocervical cells in the Cytobrush plus Ayre spatula and the Cervex brush methods, compared with the cotton swab plus Ayre spatula group (p = 2.39 x 10(-6), p = 4.49 x 10(-7) respectively). There was no statistically significant difference between the Cytobrush-Ayre spatula and the Cervex brush sampling methods were equally effective in obtaining endocervical cells in Papanicolaou smears.
Keywords: Adult; Female; Humans; Papanicolaou Test; Vaginal Smears